The Role of Infection and Inflammation in Stillbirths: Parallels with SIDS? - Blackwell, Caroline (Frontiers in Immunology, 2015)
It has been suggested that stillbirths are part of the spectrum of infant deaths than includes Sudden Infant Death syndrome (SIDS). This paper examines the hypothesis that risk factors associated with stillbirths might contribution to dysregulation of inflammatory responses to infections that could trigger the physiological events leading to fetal loss. These include genetic factors (ethnic group, sex), environmental (infection, cigarette smoke, obesity) and developmental (testosterone levels) factors. Interactions between the genetic, environmental and developmental risk factors are also considered, e.g., the excess of male stillborn infants in relation to the effects of testosterone levels during development on pro-inflammatory responses. In contrast to SIDS, inflammatory responses of both mother and fetus need to be considered. Approaches for examining the hypothesis are proposed.